Synthesis of a novel flame retardant with phosphaphenanthrene and phosphazene double functional groups and flame retardancy of poly (lactic acid) composites - Bao, Dong Mei; Wang, Jian Hang; Hou, Ze Ming; Xu, Zhi Yan; Ye, Xiao Lin; Qi, Yu Zhao; Xu, Song Jiang; Long, Li Juan; Wu, Zhong Li; Wen, Zhu (Frontiers in Materials, 2022)
A novel flame retardant hexa (4- (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10 -sulfide)-hydroxymethylphenoxy) cyclotriphosphazene (HAP-DOPS) with double functional groups was synthesized, and poly (lactic acid) (PLA) composites were prepared by melt extrusion. The flame retardancy and thermal degradation behavior of flame retardant PLA composites were studied by limiting oxygen index (LOI), vertical burning test (UL-94), cone calorimeter test (CCT), and thermogravimetric-infrared spectroscopy analysis (TG-IR). The experimental results showed that HAP-DOPS had a good flame-retardant effect on PLA. At flame retardant content of 5 wt%, the PLA/HAP-DOPS composite achieved a V-0 rating (UL-94, 3.2 mm) and a LOI value of 26.6%. The heat release rate (HRR) and total heat release (THR) of PLA composites were decreased by adding HAP-DOPS. The flame retardancy index (FRI) of PLA/HAP-DOPS-7.5 wt% was 1.0257, which showed good flame retardancy. The results of TG-IR showed that HAP-DOPS mainly had a gas-phase flame-retardant effect in PLA.